Beamforming Design for Secure IRS-Assisted Multiuser MISO Systems - Xu, Dongfang; Ng, Derrick Wing Kwan; Schober, Robert (wiley, 2024)
Recent advancements in radio frequency (RF) material have led to significant development of intelligent reflecting surfaces (IRSs) or programmable metasurfaces, which have garnered significant attention in wireless communications research. These surfaces are thin, rectangular metasurfaces that consist of sub-wavelength components that are capable of flexibly altering reflecting angle of incoming signals. By coordinating the phase shift elements, we can manipulate adverse wireless channel conditions to facilitate signal enhancement or interference mitigation. In this chapter, we leverage the programmability of IRSs for security provisioning in a multiuser wireless system comprising multiple legitimate users and an eavesdropper. To this end, a signal combining an information signal and an artificial noise (AN) is generated at the base station (BS) for security provisioning. In order to achieve security provisioning in the considered network, the IRS reflection pattern and the BS transmit beamformers are designed collaboratively. As such, an optimization problem, subject to a maximum power allowance for the BS, is formulated. Subsequently, exploiting alternating optimization theory, a low-complexity algorithm is developed to circumvent the non-convexity, producing a stationary solution. The experimental results demonstrate that our scheme overwhelms two easy-to-implement benchmarks, one with random IRS reflection pattern and another without AN. Furthermore, our results confirm that by smartly employing IRSs, we can achieve secure communication in future wireless networks.
CRIS-Team Scopus Importer:2024-12-06